José Veríssimo Dias de Matos : um crítico na direção do Gymnasio Nacional - Alves, Rosana Llopis (2008)
The work investigates, in a historical perspective, the life and the pedagogical work of José Verissimo Dias de Mattos. It privileges his performance head of the Gymnasio Nacional , the republican version of Colégio Pedro II , between 1892 and 1898. Verissimo was born in Pará, where he has directed from 1884 to 1890 the Colégio Americano , a respected establishment. In 1890, he became the director of Instrução Pública do Pará . These functions gave him the indispensable elements to elaborate a book of expressive repercussion - A Educação Nacional . His recognized experience in the education field gave him the credentials for the indication to the function of Gymnasio Nacional s Director. This research concludes that, during the time that José Veríssimo has directed this school, he analyzed the Brazilian secondary instruction, denouncing its deficiencies and indicating its resolutions.